Convenient, metal-free ipso-nitration of arylboronic acids using nitric acid and trifluoroacetic acid. Issue 1 (2nd January 2017) - Shen, Guodong; Zhao, Lingyu; Liu, Wanxing; Huang, Xianqiang; Song, Huina; Zhang, Tongxin
ABSTRACT: A feasible protocol for the direct ipso -nitration of arylboronic acids using trifluoroacetic acid and nitric acid as nitration reagent has been developed. Various aromatic nitro compounds are produced in moderate to good yields under the metal-free conditions. The method is operationally simple and regioselective, and might have potential application in industry. GRAPHICAL ABSTRACT: